2005
DOI: 10.1177/1077558705277379
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hospitalists on the Cost and Quality of Inpatient Care in the United States: A Research Synthesis

Abstract: There is substantial disagreement regarding the impact of hospitalists on costs, quality, and satisfaction with inpatient care. The authors reviewed 21 evaluations of the use of hospitalists in U.S. hospitals. Most evaluations found that patients managed by hospitalists had lower total costs or charges than patients in comparison groups and that these savings were achieved primarily by reducing length of stay. Most evaluations found no statistically significant differences in quality of care or satisfaction. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
95
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 29 publications
3
95
0
Order By: Relevance
“…4 Over the last decade, data supporting the role of hospitalists in improving quality of care for adult patients has continued to accumulate. [5][6][7][8] A 2007 retrospective cohort study by Lindenaur et al 7 included nearly 77,000 adult patients and found small reductions in length of stay without adverse effects on mortality or readmission rates, and a 2009 systematic review by Peterson 6 included 33 studies and concluded that ''in general . .…”
Section: Discussionmentioning
confidence: 99%
“…4 Over the last decade, data supporting the role of hospitalists in improving quality of care for adult patients has continued to accumulate. [5][6][7][8] A 2007 retrospective cohort study by Lindenaur et al 7 included nearly 77,000 adult patients and found small reductions in length of stay without adverse effects on mortality or readmission rates, and a 2009 systematic review by Peterson 6 included 33 studies and concluded that ''in general . .…”
Section: Discussionmentioning
confidence: 99%
“…In an assessment of hospitalists in US hospitals, Coffman and Rundall [17] concluded that patients managed by hospitalists had lower total costs due to reductions in the length of stay, rather than improvements in the quality of care or satisfaction in comparison to other groups. These findings are also confirmed by a systematic review by White and Glazier [18] concluding that hospitalists are effectual providers of inpatient care, by decreasing the length of stay (69%), and overall hospital expenses (70%), but continue to have questionable quality of care compared to that of their contemporaries.…”
Section: The Cons Of Hospital Medicine and Hospitalistsmentioning
confidence: 99%
“…Their involvement in patient care may produce reductions in length of stay, greater efficiency in discharge planning, and significant cost savings. [35][36][37] Hospitalists may also improve throughput in emergency departments and decrease wait times, leading to more efficient bed utilization. 38 This leads to a potential for greater hospital revenue by increasing both the number of admissions, particularly surgical cases, and staffed inpatient beds, the latter a premium, as AMCs continue to expand their bed capacity almost annually.…”
Section: Amcs and Hospital Performancementioning
confidence: 99%